Bimodular auxin response controls organogenesis in Arabidopsis - De Smet, Ive (National Academy of Sciences, 2010)

(untitled)
Like animals, the mature plant body develops via successive sets of instructions that determine cell fate, patterning, and organogenesis. In the coordination of various developmental programs, several plant hormones play decisive roles, among which auxin is the best-documented hormonal signal. Despite the broad range of processes influenced by auxin, how such a single signaling molecule can be translated into a multitude of distinct responses remains unclear. In Arabidopsis thaliana, lateral root development is a classic example of a developmental process that is controlled by auxin at multiple stages. Therefore, we used lateral root formation as a model system to gain insight into the multifunctionality of auxin. We were able to demonstrate the complementary and sequential action of two discrete auxin response modules, the previously described SOLITARY ROOT/INDOLE-3-ACETIC ACID (IAA)14-AUXIN REPONSE FACTOR (ARF)7-ARF19–dependent lateral root initiation module and the successive BODENLOS/IAA12-MONOPTEROS/ARF5–dependent module, both of which are required for proper organogenesis. The genetic framework in which two successive auxin response modules control early steps of a developmental process adds an extra dimension to the complexity of auxin’s action.